Lewy body dementia - McKeith, Ian (Henry Stewart Talks, 2010)
Dementia with Lewy bodies (DLB), Parkinson's disease dementia (PDD), Clinical and pathological diagnosis, Cerebral spinal fluid (CSF) and imaging biomarkers, Clinical progression, Treatment options